Quercetin attenuates nicotine-induced ovarian and uterine dysfunction in rats - Elmira Sayad; Masoumeh Faghani; Parvaneh Keshavarz; Ali Rafiei; Fahimeh Mohammadghasemi (Clinical and Experimental Reproductive Medicine, 2026)
Objective: Nicotine, a principal constituent of tobacco smoke, disrupts female reproductive physiology. Quercetin, a flavonoid with both phytoestrogenic and antioxidant properties, may counteract this toxicity. This study aimed to evaluate the histological, biochemical, and molecular effects of quercetin co-administration with nicotine on ovarian and uterine tissues in rats.Methods: Thirty-two female Wistar rats were assigned to four groups: control, nicotine-treated (1 mg/kg), quercetin-treated (15 mg/kg), and a combined nicotine (1 mg/kg)–quercetin (15 mg/kg) group. Histopathological assessments were performed alongside biochemical analyses of oxidative stress markers—malondialdehyde (MDA), superoxide dismutase (SOD), and total antioxidant capacity (TAC)—and enzyme-linked immunosorbent assay (ELISA)-based hormonal profiling. Immunohistochemistry was employed to quantify estrogen receptor-alpha (ERα) and Ki-67 expression.Results: Co-administration of nicotine and quercetin increased uterine wall thickness and was associated with elevated estradiol levels, reduced MDA activity, and increased SOD and TAC in both uterine and ovarian tissues compared with the nicotine group. The nicotine–quercetin group also showed a lower Ki-67 index in ovarian follicles and stroma, along with a marked reduction in atretic follicles. Conversely, there were significant increases in antral follicles, corpus luteum formation, and ERα expression in the uterine endometrium and epithelium, as well as in the ovarian stroma and corpus luteum, versus the nicotine-only group.Conclusion: Quercetin (15 mg/kg) appears to protect against nicotine-induced reproductive impairments (1 mg/kg), likely through its antioxidant properties, its capacity to stabilize hormone levels, and its modulation of ERα and Ki-67 expression. These findings support quercetin’s therapeutic potential for preventing or alleviating smoking-related reproductive damage.